PELAKSANAAN LAYANAN BIMBINGAN KONSELING DI SEKOLAH DASAR ISLAM NURUL ISLAM - Terra Nurlatipah; Nasichah, Sheyla Aulia Sagita, Akbar Nicholas Saputra, Muhammad Hudan Raya (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2024)
Research conducted at SDI Nurul Islam focused on the implementation of counseling guidance services at nurul islam Islamic elementary school. This research aims to objectively understand the situation of guidance and counseling in the school. The results of the interview with the Principal, revealed that guidance and counseling services involve various types, such as orientation, information, individual counseling, groups, and mediation. Class teachers also have a significant role in providing guidance and counseling. This research is a qualitative study that uses observation, interview, and documentation methods. Overall, this study provides an overview of the implementation of guidance and counseling services at SDI Nurul Islam. It was found that the role of teachers, especially class teachers, is very influential in helping students overcome problems. However, the study also highlighted the need for improvement in the thoroughness of guidance and counseling services, with a plan to develop specialized teachers to support students more optimally.